Conservation of pūpū whakarongotaua - the snail that listens for the war party - Daly, Elizabeth E; Trewick, Steven Alexander; Dowle, Eddy J; Crampton, James S; Morgan-Richards, Mary (Ethnobiology and Conservation, 2020)
Snail ecotypes are an indicator of local forms that can have cultural value and also represent evolutionary potential. Conservation of both regional diversity and evolutionary potential can be improved by recognition and documentation of genetically determined phenotypic variation. The large threatened terrestrial snail pūpū whakarongotau (Placostylus ambagiosus) is a range restricted species that is valued by the indigenous people of the northern most region of New Zealand, valued as both a security alarm and food source. Some populations of this rare species are restricted to sites of human occupation and oral history suggests these distinct populations represent prehistoric translocations. We used 2-D geometric morphometrics and nuclear markers to document the distribution of variation. We aimed to determine whether shell shape variation was entirely an ecophenotypic plastic response, and whether or not prehistoric human movement of snails and establishment of food populations on pā sites (fortified settlements) had resulted in the loss of spatial genetic structure within this species. We could discriminate specimens due to shape variation among population samples. Using samples from prehistoric sites we infer shell shape in this species is not purely a plastic response to the local environment but reveals evolutionary potential. Genotypes with 1738 nuclear loci for 19 individuals from ten locations revealed some evidence of population mixing, but genetic variation was mostly partitioned among locations, with strong spatial structure revealed. Thus, we advocate conservation measures that will preserve will local forms that represent evolutionary potential of this species.